Examining the Socio-Economic Impact of Road Infrastructure Development: A Case Study of Donri-Donri District, Soppeng Regency - Nur Amalia; Sitti Jamiah HA (Pustaka Digital Indonesia, 2024)
Infrastructure development, particularly road infrastructure, plays a vital role in fostering economic growth and improving the quality of life in communities. This study examines the socio-economic impact of road infrastructure development on increasing community income in Pesse Village, Donri-Donri District, Soppeng Regency. Utilizing a quantitative-descriptive approach, data was collected through questionnaires distributed to 91 respondents from the Pesse Village community and analyzed using multiple linear regression in SPSS. The findings reveal a significant positive correlation between road infrastructure development and increased community income in Pesse Village. The regression analysis indicates that road infrastructure development has a substantial influence on income growth, with a regression coefficient of 0.563. Moreover, the research underscores the importance of continuous infrastructure improvements in enhancing the economic well-being of local communities. This study contributes to the existing body of knowledge by providing empirical evidence of the socio-economic benefits associated with road infrastructure development. The results emphasize the need for policymakers to prioritize infrastructure investments as a means of fostering economic development and improving livelihoods at the grassroots level.